2018
DOI: 10.3390/cells7060061
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of the Transient Receptor Potential Vanilloid (TRPV) Channels 1, 2, 3 and 4 in Mucosal Epithelium of Human Ulcerative Colitis

Abstract: The Transient Receptor Potential (TRP) family of selective and non-selective ion channels is well represented throughout the mammalian gastrointestinal track. Several members of the Transient Receptor Potential Vanilloid (TRPV) subfamily have been identified in contributing to modulation of mobility, secretion and sensitivity of the human intestine. Previous studies have focused on the detection of TRPV mRNA levels in colon tissue of patients with inflammatory bowel disease (IBD) whereas little information exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 48 publications
4
40
0
Order By: Relevance
“…Intestinal cells are not expected to express a significant level of endogenous TRPV4 [40], and expression of WT TRPV4 already conferred a slight increase in invasive capacity, as already reported [31]. TRPV4 S823D, S824D, and T813D conferred a strong gain in invasion (Figure 2(c,e)).…”
Section: Conservation Of Ohnologs For Trp Family Memberssupporting
confidence: 70%
“…Intestinal cells are not expected to express a significant level of endogenous TRPV4 [40], and expression of WT TRPV4 already conferred a slight increase in invasive capacity, as already reported [31]. TRPV4 S823D, S824D, and T813D conferred a strong gain in invasion (Figure 2(c,e)).…”
Section: Conservation Of Ohnologs For Trp Family Memberssupporting
confidence: 70%
“…Further study confirmed an increased expression of TRPV1 in inflamed tissue of active UC patients compared with noninflamed tissue, being associated with a relapse and continuous activity of disease (64,67). However, a downregulated expression of TRPV1 was also revealed in colonic biopsies from UC and CD patients (68,70,71), and Rizopoulos et al (70) found no significant correlation between TRPV1 expression and clinical features in UC patients. In experimental colitis models, TRPV1 expression was also found to be altered (68, 78-80, 83, 84, 86) ( Table 1).…”
Section: Trpv1mentioning
confidence: 83%
“…The TRPV4 mRNA expression and TRPV4 immunoreactivity in colon were remarkably upregulated in IBD patients (70,72,76), in particular, serosal blood vessels with active inflammation were more densely innervated by TRPV4-positive fibers, which often co-localized with the infiltrating CD45 + cells (73,76). Meanwhile, TRPV4 activation could recruit macrophages and other immune cells through the induction of chemokines, such as IL-8 and MCP-1 (73).…”
Section: Trpv4mentioning
confidence: 99%
“…Most in vivo studies targeting TRPV1 in animal models of atherosclerosis use dietary capsaicin treatment to achieve improvement either in atherosclerotic plaque reduction or in the accompanying inflammation. As we indicated in the above section, oral capsaicin treatment cannot directly act on cardiac or intravascular TRPV1 receptors, therefore, a remote activation should be suggested, which likely involves TRPV1 receptors localized on the capsaicin-sensitive sensory nerve terminals [ 68 ] and/or the intestinal epithelial cells [ 69 ]. The ApoE −/− mouse is the most frequently used model to study atherosclerosis [ 70 ].…”
Section: The Capsaicin-sensitive Sensory Nerves and The Trpv1 Recementioning
confidence: 99%